2022
DOI: 10.1037/pspp0000412
|View full text |Cite
|
Sign up to set email alerts
|

Gain- but not loss-related self-perceptions of aging predict mortality over a period of 23 years: A multidimensional approach.

Abstract: Some 2 decades have passed since Levy et al. (2002) published their seminal study on the impact of selfperceptions of aging (SPA) on mortality over a period of 23 years in this journal; we aimed at replicating and extending these findings against the background of recent discussions in the research on subjective aging. Based on a large German nationwide population-based sample of individuals aged 40 and older (N = 2,400), for whom mortality was also documented over a period of 23 years , the present study is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 96 publications
0
13
0
Order By: Relevance
“…Wurm & Schäfer (2022) recently found that gain-related (i.e., positive) SPA, but not loss-related (i.e., negative) SPA, was associated with mortality 23 years later. As such, reductions in positive SPA following a marital loss may have serious health-related consequences despite not being paired with increases in negative SPA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wurm & Schäfer (2022) recently found that gain-related (i.e., positive) SPA, but not loss-related (i.e., negative) SPA, was associated with mortality 23 years later. As such, reductions in positive SPA following a marital loss may have serious health-related consequences despite not being paired with increases in negative SPA.…”
Section: Discussionmentioning
confidence: 99%
“…Brown and colleagues (2021), for example, found that positive, but not negative, SPA predicted cognitive functioning amongst older adults. Likewise, a recent study showed that gain-related (i.e., positive) SPA, but not loss-related (i.e., negative) SPA was associated with mortality 23 years later (Wurm & Schäfer, 2022). Because marriage is so highly gendered, marital status transitions differ demographically by gender, and men and women experience positive and negative SPA in different ways, studying gender differences in marital status transitions and their connections to positive and negative SPA, specifically, rather than SPA in general, is important.…”
Section: Gender Differences and Positive Spa Versus Negative Spamentioning
confidence: 91%
“…Furthermore, it dates back to the fundamental insight by Baumeister et al (2001) and an extensive body of research that negative experiences and evaluations tend to have more impact on behavior than positive ones. Although a recent study found stronger support for adults’ perceptions of age-related gains as predictors of longevity (Wurm & Schäfer, 2022), other studies have shown stronger associations between age-related losses and markers of health (Brothers et al, 2017, 2019; Dutt, Gabrian, & Wahl, 2018).…”
Section: Previous Researchmentioning
confidence: 98%
“…Resilience is important in both young and old age, because global disruptions, such as the pandemic, can occur during a critical phase in young people's emotional and social development or add to naturally occurring disruptions in older people (e.g., retirement and/or physical/cognitive impairments). We advocate for more collaborative action, combining expertise from child and adult resilience research [ 56 ] and leveraging existing knowledge in the field of healthy aging, which has already addressed positive psychological concepts that could be viewed as age-related resilience factors (e.g., views on aging [ 114 , 115 ]).…”
Section: Lessons Learned For Research On Resiliencementioning
confidence: 99%